Analisis Penggunaan Model SOSTAC pada Strategi Pemasaran Daring di TikTok Shop akun Nadiraa - Dewi Lely Ambarwati; Niken Alifiana; Pilin Pilin (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Today's technology is increasingly sophisticated and can even be used as a means for marketing media. Many business owners utilize this technology as a medium for product promotion. One of them is Nadiraa who participated directly to do online marketing at TikTok Shop. The purpose of this study is to determine the use of the SOSTAC model in the online marketing strategy at TikTok Shop Nadiraa's account. The method used in the research is qualitative research method with descriptive method. The subject of this research is Nadiraa's TikTok Shop account, and the object of this research is the Analysis of the Use of the SOSTAC Model on the Online Marketing Strategy at TikTok Shop Nadiraa's account. The data collection technique in this research is using content analysis on Nadiraa's account at TikTok Shop. The results in this study show that there are results of an analysis of online marketing strategies using the SOSTAC method on Nadiraa's account as a whole starting from Situation Analysis using SWOT analysis, then Objectives with 5S analysis, Strategy with STP analysis, Tactics using 4P, Action analysis of actions taken by Nadiraa, and finally controlling as material for evaluation to be able to increase profits. Keywords: , ,